Design and Thermo-Economic Analysis of an Integrated Solar Field Micro Gas Turbine Biomass Gasifier and Organic Rankine Cycle System - Roberta De Robbio; Maria Cristina Cameretti; Salvatore Agizza (Energies, 2023)
A micro gas turbine (MGT) is an advanced technology with a simple structure and fast load response. It represents a good choice for the next generation of distributed power systems, where fossil fuels are going to be largely replaced by biofuels and renewable sources. In this context, this work aims to investigate and compare the performance of gradually more complex energy systems integrating a micro gas turbine plant: simple cogenerating asset, integrating a solar field, presence of a gasifier, and the addition of a bottoming ORC. In all cases, a thermo-economic analysis has been carried out for an application in the agricultural sector. Agricultural waste can be used to create a syngas as fuel for MGT through a gasifier, promoting the utilization of carbon-neutral alternative fuels to reduce harmful emissions. The authors considered the electrical and thermal needs of a hypothetical agri-food company to build the electrical and thermal load curves. The new and more complex cogeneration plant, designed by using the Thermoflex 30 software, leads to an increase in electrical power, recovered thermal power, overall electrical efficiency, carbon neutrality, and cogeneration indexes. In particular, the presence of the solar field promotes a reduction in fuel consumption as well as greater heat input to the thermal unit. The addition of a bottoming ORC system increases the electrical power by 36.4%, without significantly penalizing the thermal unit. Moreover, thanks to the gasifier that offsets the fuel reduction costs, through an economic analysis of the entire plant, a payback time of the investment of less than 4 years is obtained.